2001
DOI: 10.1074/jbc.m103664200
|View full text |Cite
|
Sign up to set email alerts
|

Location and Mechanism of α2,6-Sialyltransferase Dimer Formation

Abstract: A significant proportion of the ␣2,6-sialyltransferase of protein Asn-linked glycosylation (ST6Gal I) forms disulfide-bonded dimers that exhibit decreased activity, but retain the ability to bind asialoglycoprotein substrates. Here, we have investigated the subcellular location and mechanism of ST6Gal I dimer formation, as well as the role of Cys residues in the enzyme's trafficking, localization, and catalytic activity. Pulse-chase analysis demonstrated that the ST6Gal I disulfidebonded dimer forms in the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Autopolysialylation of the polysialyltransferases may be somewhat different mechanistically and yet still rely on protein-protein interactions in the form of enzyme dimerization or oligomerization. In support of this idea, many glycosyltransferases form dimers (73)(74)(75)(76), and another ␣2,8-sialyltransferase, ST8Sia III, is also capable of autopolysialylation even though it does not polysialylate NCAM or any other glycoprotein substrate (39). We predict that these three ␣2,8-sialyltransferases form dimers or higher order oligomers, and this type of protein-protein interaction allows them to autopolysialylate their own oligosaccharides.…”
Section: Discussionmentioning
confidence: 74%
“…Autopolysialylation of the polysialyltransferases may be somewhat different mechanistically and yet still rely on protein-protein interactions in the form of enzyme dimerization or oligomerization. In support of this idea, many glycosyltransferases form dimers (73)(74)(75)(76), and another ␣2,8-sialyltransferase, ST8Sia III, is also capable of autopolysialylation even though it does not polysialylate NCAM or any other glycoprotein substrate (39). We predict that these three ␣2,8-sialyltransferases form dimers or higher order oligomers, and this type of protein-protein interaction allows them to autopolysialylate their own oligosaccharides.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, ␤3GalT1, ␤3GalT5, and the homologous Drosophila protein Brainiac also contain Cys residues in their putative transmembrane domains, but the function of these residues is unknown. One possibility is that they may affect the oligomerization of the protein as recently reported for ␣2,6-sialyltransferase I (36). The transmembrane domain is followed by a segment rich in Ser, Pro, Ala, and Gly, which has been described as the "SPLAG" domain in other transferases (37), and presumably represents a stem region that determines the distance between the catalytic domain and the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Other GTs from the trans- Golgi ␤4-Galactosyltransferase has been shown to form homodimers mediated by Cys-29 and/or His-32 from the TM, and dimerization was associated with Golgi localization (28). On the other hand, ␣2,6-sialyltransferase has been shown to dimerize through Cys-24 from its TM, dimerization not being required for Golgi localization or enzyme activity, but possibly necessary to induce higher multiplicity oligomerization (9). For FT3, it was found that mutation of Cys-29 led to increased levels of expression on the PM (FT3np2).…”
Section: Discussionmentioning
confidence: 99%
“…The luminal domain of GTs has also been shown to be important for the formation of protein-protein complexes. It has been observed that cis/medial GTs form large insoluble oligomers, contrary to late Golgi GTs that usually exist as dimers (7)(8)(9). Furthermore, changing the targeting of cis/medial Golgi mannosidase II to the endoplasmic reticulum (ER) leads to accumulation of N-acetylglucosaminyltransferase I in the ER (7,10) in a kin-recognition mechanism.…”
Section: Glycosyltransferases (Gts)mentioning
confidence: 99%